C-reactive protein and alpha 1-acid glycoprotein levels in dogs infected with Ehrlichia canis. - Rikihisa, Y (1994)
To elucidate whether acute-phase protein responses occur in dogs infected with Ehrlichia canis, C-reactive protein (CRP) and alpha 1-acid glycoprotein (AAG) levels were serially measured in the plasma of five dogs experimentally inoculated with E. canis and 10 sham-inoculated or noninoculated control dogs. The CRP concentration was measured by a canine-specific capture enzyme-linked immunosorbent assay, and the AAG concentration was measured by a canine-specific radial immunodiffusion method. In all E. canis-inoculated dogs, a 3.3- to 6.5-fold increase in the plasma CRP concentration and a 1.9- to 8.6-fold increase in the plasma AAG concentration over the preinoculation level occurred at days 4 to 6 postexposure. Despite the persistence of E. canis and high antibody titers, both CRP and AAG concentrations gradually declined to preexposure levels by day 34 postexposure. E. canis-infected dogs had mild and transient clinical signs which resolved without treatment by day 14 postexposure. The CRP and AAG concentrations in control inoculated or nontreated dogs remained within the normal range throughout the experimental period. Of 12 dogs naturally infected with E. canis, 75% had greater than 50 micrograms of CRP per ml and 83% had greater than 500 micrograms of AAG per ml. All of these 12 dogs had chronic and severe clinical signs of canine ehrlichiosis. Thus, elevations in the levels of acute-phase proteins occur in both acute and chronic canine ehrlichiosis. Determination of CRP and AAG concentrations may help in assessing the severity of inflammatory damage in dogs with E. canis infections.